PUNA Aircraft Static Stability Simulation Using XFLR5 Software - Bangga Dirgantara Adiputra; Agus Rohmanto (Institut Teknologi Dirgantara Adisutjipto, 2022)
Currently the development of Uncrewed Aircraft is experiencing a very rapid increase. This is demonstrated by the large number of use of Unmanned Aircraft in several sectors, one of which is for monitoring traffic density. On this mission the aircraft will carry a payload in the form of a camera used to record or display the existing traffic situation. This mission requires aircraft with good stability capabilities so as to be able to provide good monitoring results. So it is necessary to analyze the static stability in longitudinal, lateral and directional motion. Static stability simulation was carried out with the help of XLFR5 software. The simulation results are then compared with the parameters that are a requirement for longitudinal, lateral, and directional static stability.